Cultural capital and academic success of migrant students in technical-vocational secondary education on the northern border of Chile - Mondaca Rojas, Carlos (2025)
The role of the cultural capital of migrant students in technical and vocational secondary education in northern Chile and its influence on academic success are examined. A qualitative research approach was used (interviews and focus groups). A profile of migrant students characterized by their effort, discipline, and good performance was identified. It is argued that their cultural diversity could be an asset that provides them with access to resources and opportunities and facilitates recognition by teachers. The findings underscore the need to integrate this cultural capital into educational policies, thus promoting inclusive and quality education.